PENERAPAN KAJIAN KITAB AL-BAHJAH AL-MARDHIYAH FĪ AL-AKHLAK AD- DINIYAH DALAM PEMBENTUKAN KARAKTER RELIGIUS SISWADI SMA NEGERI 1 MUARA HARUS - Pahrurraji Pahrurraji (CV. ADIBA AISHA AMIRA, 2023)
This research is motivated by the application of the study of the book al-Bahjah Al-Mardhiyah fī al- Akhlak Ad-Diniyah in formal educational institutions in the formation of students' religious character. SMA Negeri 1 Muara Harus apply the book study with regular learning to support the program at school. Book study at SMA Negeri 1 Muara Harus is a program that applies Islamic boarding school learning which is very rarely done in other formal education. This study aims to determine the application of the study of the book al-Bahjah al-Mardhiyah fī al-Akhlak ad-Diniyah in the formation of the religious character of students at SMA Negeri 1 Muara Harus and to determine the supporting and inhibiting factors. This study used a qualitative descriptive approach and a type of field research. The informants of this research were school principals, religious teachers (PAI), and study teachers and students. The data collection techniques were obtained through observation, interviews and documentation. While data analysis by means of data reduction, data presentation, and verification. Based on the research results it can be concluded that; 1) planning is done by reading the book first. Furthermore, the implementation of the book study was followed by all students every wednesday after the midday prayer in congregation with a time of 10-20 minutes. Finally, there is an evaluation through the results of observations that most students have seen changes in their religious character, such as their belief and awareness of carrying out worship as a form of obligation, to the teacher being more respectful when walking in front of them bowing their bodies, greeting when they meet, good manners and character to his friend. Although there are some students who have not applied religious character, especially to teachers, such as feeling unhappy because they are always regulated. 2) The supporting and inhibiting factors, such as the supporting factors are the ability and willingness of the study teachers, most of the students are enthusiastic about participating in the study of the book, and a beautiful or cool environment plus adequate school facilities. As for the inhibiting factors, there is still a lack of a study team or instructor, students who feel tired or bored, and unexpected things happen, such as power outages.